Kultur Embrio Mencit In Vitro: Studi Perbandingan Efektifitas Media M16 dan CZB - Foenna, Yudi Gebri; Nasution, Jamilah (Universitas Medan Area, 2024)
Successful embryo culture is influenced by culture methods and conditions, which have an impact on cytoplasmic factors and the ability of embryo development. This study aims to compare the effectiveness of two culture mediums, M16 and CZB, in supporting the development of DDY strain mice embryos in vitro. The research method used was an experimental study consisting of animal husbandry, medium culture preparation, superovulation, collection, and in vitro embryo culture. Data analysis in this study used descriptive statistical tests to measure embryo development in each culture medium, M16 and CZB, in observations for 96 hours with a 24-hour interval using an inverted microscope. The results showed that embryos in the CZB medium experienced 50% development of the expanded blastocyte stage after 96 hours of culture with 50% degenerative. In the M16 culture medium, 0% of embryos experienced embryonic stage development after 96 hours of culture and 100% were degenerative. This study has concluded that the development of embryos in vitro in the M16 culture medium was not better than CZB, this was evidenced by the percentage at the expanded blastocyte development stage.